2008
DOI: 10.1007/s11139-008-9142-0
|View full text |Cite
|
Sign up to set email alerts
|

On the divisor function and the Riemann zeta-function in short intervals

Abstract: Abstract. We obtain, for T ε ≤ U = U(T ) ≤ T 1/2−ε , asymptotic formulas forwhere ∆(x) is the error term in the classical divisor problem, and E(T ) is the error term in the mean square formula for |ζ( 1 2 + it)|. Upper bounds of the form O ε (T 1+ε U 2 ) for the above integrals with biquadrates instead of square are shown to hold for T 3/8 ≤ U = U(T ) ≪ T 1/2 . The connection between the moments of E(t + U) − E(t) and |ζ( 1 2 + it)| is also given. Generalizations to some other number-theoretic error terms are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
33
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 24 publications
5
33
0
Order By: Relevance
“…The behaviour of the exponential sums is extremely intriguing: One might expect square-root cancellation, and while this is not an unreasonable assumption in the GL(2) setting when ∆ ≪ M 1/2 , Ernvall-Hytönen [4] has proved that where c ∈ R + is an arbitrary fixed coefficient. This Ω-result extends the earlier work by Ivić [15] (see also [19]), where he has shown that for ∆ = o( √ M ). While upper and lower bounds are relatively widely studied in the GL (2) setting (see e.g.…”
Section: Exponential Sums Related To Cusp Formssupporting
confidence: 89%
“…The behaviour of the exponential sums is extremely intriguing: One might expect square-root cancellation, and while this is not an unreasonable assumption in the GL(2) setting when ∆ ≪ M 1/2 , Ernvall-Hytönen [4] has proved that where c ∈ R + is an arbitrary fixed coefficient. This Ω-result extends the earlier work by Ivić [15] (see also [19]), where he has shown that for ∆ = o( √ M ). While upper and lower bounds are relatively widely studied in the GL (2) setting (see e.g.…”
Section: Exponential Sums Related To Cusp Formssupporting
confidence: 89%
“…Ivić [7] gives a more precise formula for the left-hand side of (1.3) that includes lower order terms and an error term with a power savings in X. We can also prove more precise formulas than those stated in Theorems 1.1 and 1.2.…”
Section: Introduction and Main Resultsmentioning
confidence: 87%
“…However, this upper bound is most likely not sharp and the true order of magnitude is probably of size (X 1− 1 k /L) · (log L) k 2 −1 . More precise estimates than (1.2) in the case that k = 2 are given by Jutila [8] and Ivić [7] (see also [1] and [9]). In particular, Ivić [7] derives an explicit asymptotic formula for the variance of sums of d 2 (n) = d(n) in short intervals with x < n ≤ x + h and…”
Section: Introduction and Main Resultsmentioning
confidence: 99%
“…The interesting range for us is that of shorter intervals: H < X 1− 1 k . For k = 2, Jutila [20], Coppola and Salerno [8], and Ivić [18,19] show that, for X ǫ < H < X 1/2−ǫ , the mean square of ∆ 2 (x, H) is asymptotically equal to…”
Section: Introductionmentioning
confidence: 99%